Kedudukan Dan Mekanisme Verzet Terhadap Penetapan Diversi Dalam Perspektif Hukum Pidana Anak Di Indonesia - Aditya, M. Fachri; Nashriana, Nashriana; Febriansyah, Artha (Consensus : Jurnal Ilmu Hukum, 2026)
The development of the juvenile criminal justice system in Indonesia has shifted from a retributive to a restorative approach through the implementation of diversion as regulated under Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. In practice, however, diversion decisions are not always accepted by the parties involved, giving rise to the need for a legal mechanism known as verzet, which remains unclear in positive law. This study aims to analyze the legal status of verzet against diversion decisions, its procedural mechanism, and the juridical and practical obstacles encountered in its application. The research employs a normative legal method with statutory and conceptual approaches, using qualitative analysis of primary, secondary, and tertiary legal materials. The findings indicate that the legal status of verzet is still ambiguous due to the absence of explicit legal basis, while its procedural mechanism lacks standardized guidelines and is applied interpretatively in practice. Additionally, obstacles include normative gaps and conceptual conflicts juridically, as well as limited understanding among law enforcement officers and societal legal culture practically. Therefore, comprehensive regulation on verzet is necessary to ensure legal certainty while upholding the principles of child protection within the juvenile criminal justice system in Indonesia.